Modality Used in Beauty Product Advertisements on Instagram Caption (LINGUISTIK TERAPAN, 2020)
This research was carried out to investigate the modality used in beauty product advertisements on Instagram caption. The objective of the research was to describe the types of modality used in beauty product advertisements on Instagram caption. The data of this research was the clauses consisting of modality used in beauty product advertisements which are taken from official account of three local brands on Instagram. Descriptive qualitative method was used in this research. The instrument of this research was observation. The types of modality were analyzed by using the theory of Carrettero (2007). In this research was found four types of modality. The types were found in this research, namely Epistemic, Deontic, Dynamic, and Boulomaic.Keywords: Types of Modality, Beauty Product Advertisements, Instagram Caption